Impact of clinical pharmacist-led interventions on glycemic control and quality of life among Iraqi patients with type 1 diabetes mellitus - Marwa Salman Abd Alrahman; Ali Lateef Jasim; Muqdad A. Alhilal (Pharmacia)
Adequate glycemic management reduces complications related to diabetes and enhances the patient’s quality of life. This study intended to evaluate pharmacist-led educational initiatives on glycemic management and quality of life (QOL) in individuals with type 1 diabetes. Pharmacists have a significant effect on the treatment of people with diabetes mellitus (DM) and a vital role in the enhancement of QOL. The objective of the study is to assess the efficacy of pharmacist-led intervention (PI) on the glycemic control and QOL of adult patients with type 1 DM in Iraq. The current study is a prospective, comparative, pre-post intervention study on patients with type 1 DM who attended a Specialized Center for Endocrinology and Diabetes in Baghdad, Al-Russafa. At baseline, the glycated hemoglobin (HbA1C) and fasting blood glucose (FBS) were recorded, and the QOL was assessed by filling out the Quality-of-Life Scale for Iraqi Diabetes Mellitus Patients (QOLSID) questionnaire for each patient in both cohorts. After that, the patients in the interventional group received a face-to-face educational session, which lasted about 20–30 minutes. Then, an Arabic educational booklet was handed out to each patient in the interventional group. Three months later, the same parameters were re-measured for the same patients in both study groups. The percentage of patients demonstrating glycemic control was significantly higher than that of the control group (36.4% vs. 2.3%). The QOL score significantly increased in the intervention group (10.0% vs. 3.0%) compared to the control group. Our study concludes that a clinical pharmacist-led educational intervention may improve the glycemic control and QOL of type 1 DM.